2020
DOI: 10.1111/lam.13431
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a newly isolated Rhodotorula mucilaginosa NQ1 and its development for the synthesis of bulky carbonyl compounds by whole‐cell bioreduction

Abstract: A strain NQ1, which showed efficient asymmetric reduction of 3,5‐bis(trifluoromethyl) acetophenone (BTAP) to enantiopure (S)‐[3,5‐bis(trifluoromethyl)phenyl]ethanol ((S)‐BTPE), which is the key intermediate for the synthesis of a receptor antagonist and antidepressant, was isolated from a soil sample. Based on its morphological and internal transcribed spacer sequence, the strain NQ1 was identified to be Rhodotorula mucilaginosa NQ1. Some key reaction parameters involved in the bioreduction catalyzed by whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In addition to the bacterial strains mentioned above, 37 Wang et al reported a fungal strain, Rhodotorula mucilaginosa NQ1, isolated from soil for the reduction of 3,5-bis(trifluoromethyl)acetophenone ( 4 ) to ( S )-[3,5-bis(trifluoromethyl)-phenyl]ethanol ( 5 ) (Scheme 6). 58 After systematic optimization studies, 80 mmol L −1 of substrate 4 was reduced using 250 g (wet weight) per L of resting cells and 35 g L −1 of glucose as the cosubstrate, which led to product 5 in good isolated yield (82%) and ee (99%). In addition, reduction of substrate 4 using whole cells of strain NQ1 was scaled up with 1 L of reaction mixture in a 5 L bioreactor.…”
Section: Whole-cell Redox Biocatalysismentioning
confidence: 99%
“…In addition to the bacterial strains mentioned above, 37 Wang et al reported a fungal strain, Rhodotorula mucilaginosa NQ1, isolated from soil for the reduction of 3,5-bis(trifluoromethyl)acetophenone ( 4 ) to ( S )-[3,5-bis(trifluoromethyl)-phenyl]ethanol ( 5 ) (Scheme 6). 58 After systematic optimization studies, 80 mmol L −1 of substrate 4 was reduced using 250 g (wet weight) per L of resting cells and 35 g L −1 of glucose as the cosubstrate, which led to product 5 in good isolated yield (82%) and ee (99%). In addition, reduction of substrate 4 using whole cells of strain NQ1 was scaled up with 1 L of reaction mixture in a 5 L bioreactor.…”
Section: Whole-cell Redox Biocatalysismentioning
confidence: 99%
“…Several microorganisms have been reported in recent years, such as Cyberlindnera saturnus, [25] Sphingomonas sp., [26] Candida tropicalis, [27] Rhodotorula mucilaginosa, [28] Rhodococcus erytropolis, [29] Saccharomyces rhodotorula. [30] Medium engineering and in particular the use of deep eutectic solvents (DESs) was explored in some of these studies [25,27a,29] to overcome the problem of unsatisfactory results with whole cell biocatalysis.…”
Section: Introductionmentioning
confidence: 99%